Nitrogen use efficiency and rice yield as influenced by the application of prilled urea and urea super granule with or without organic manure (Journal of the Bangladesh Agricultural University, 2014)
An experiment was conducted to examine the effect of prilled urea (PU), and urea super granule (USG) alone or in combination with poultry manure or cowdung on NH4-N content of rice field with nitrogen use efficiency (NUE) and the yield of rice (cv. BRRI dhan50). The experiment was carried out at the Soil Science Field Laboratory of Bangladesh Agricultural University, Mymensingh during Boro season of 2012 and laid out in a randomized complete block design with three replications. There were six treatments viz. T1 (Control), T2 (78 kg N ha-1 from USG), T3 (136 kg N ha-1 from PU), T4 (58 kg N ha-1 from USG), T5 (58 kg N ha-1M from USG + 3 t ha-1 poultry manure) and T6 (58 kg N ha-1 from USG + 5 t ha-1 cowdung). All plots received recommended doses of P, K, S and Zn fertilizers. The NH4-N in rice field water increased rapidly when N was applied as PU. In contrast, NH4-N release was very slow when applied as USG over the crop growth period. Application of PU, USG alone or in combination with poultry manure or cowdung significantly influenced grain and straw yield, all the yield components except 1000-grain weight of BRRI dhan50. Urea super granule with poultry manure (treatment T5) produced the highest grain and straw yield and the lowest values were recorded from control. Nitrogen content and uptake, apparent N recovery and NUE were also influenced significantly by the application of PU, and USG alone or in combination with organic manure. Among the treatments, T5 demonstrated the highest N recovery and NUE. The overall results suggest that application of USG in combination with poultry manure could be considered more effective for increasing the yield and NUE of BRRI dhan50. DOI: http://dx.doi.org/10.3329/jbau.v12i1.21237 J. Bangladesh Agril. Univ. 12(1): 37-43, June 2014